Pendaftaran Kebaya Sebagai Warisan Tak Benda Ke UNESCO: Analisis Framing Zhongdang Pan dan Gerald M Kosicki Dalam Media Kompas.com dan Berita Satu.com - Dellya Putri Apriliany; Hendra Setiawan (Peneliti.net, 2023)
In order to analyze news and the media, this study looks into the field of journalism. As a result, the purpose of this study was to determine how each media presented an event. The information gathered in this study is analyzed and described using a quantitative descriptive method. Additionally, the news article